Social and Ecological Consequences of Nautical Marinas in Tourist Development: The Case of the Croatian Part of Adriatic Sea - Čaldarović, Ognjen (Array, 1997)
In the paper an alternative development of nautical tourism is advocated with the use of existing facilities of small harbours along the Adriatic coastline. Sociological research and methodological approach for studying marine tourism is proposed and major techniques for the research are displayed.